PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN DIVIDEN DAN INVESTMENT OPPORTUNITY SET TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2016-2018 - Ni Nyoman Yuningsih; Ni Luh Gde Novitasari (Badung: LPPM Universitas Triatma Mulya, 2020)
Financial performance can be used as a benchmark in assessing a company's financial success. Financial performance is a measure that describes the financial condition and ability of companies to make a profit. This study aims to reexamine the effect of environmental performance, corporate social responsibility, and good corporate governance on corporate financial performance. The sample in this study were 55 mining companies listed on the Indonesia Stock Exchange for the period 2014 - 2018. Determination of the sample using a purposive sampling method. The analytical tool used is multiple linear regression analysis. The results showed that environmental performance had no effect on financial performance and corporate social responsibility had a negative effect on financial performance. However, good corporate governance has a positive effect on financial performance.